A new spherical aberration coefficient C4 for the Gaussian laser beam - Bencheikh, Abdelhalim; Bouafia, Mouhamed; Ferria, Kouider (Oficyna Wydawnicza Politechniki Wrocławskiej, 2011)
Laser beam quality is related to the aberration effect. Quartic phase aberration, more commonly known as spherical aberration, can result from aberrated optical components such as beam expanding telescopes, focusing or collimating lenses, or other conventional optical elements. In general, any kind of quartic aberration will lead to increased far field beam spread, degraded laser beam focusability and increased values of the beam quality. Currently, a well established quality parameter for laser beams is the M2 factor which is proportional to the coefficient of quartic phase aberration denoted C4. In many recent papers, authors used C4 given in geometrical optics approach to evaluate the laser beam quality M2 which belongs to the Gaussian beam optics and the two disciplines are not to be confused. In this paper, we present a new mathematical set for the spherical aberration coefficient C4, especially for Gaussian beams in the context of Gaussian beam optics. A numerical analysis of a set of lenses is done to show the importance of the new C4.
Optica Applicata, Vol. 41, 2011, Nr 4, s. 855-861
Keywords: optyka; laser beam quality factor; Gaussian beam; spherical aberration